EXPRESSION OF RECOMBINANT HUMAN ERYTHROPOIETIN WITH GLYCOSYLATION MODIFICATION IN HEK293T CELLS - Endah Puji Septisetyani; Yana Rubiyana; Popi Hadi Wisnuwardhani; Andri Wardiana; Adi Santoso (Indonesian Journal of Pharmacy, 2012)
Stability  of  erythropoietin  (EPO)  depends  on  its glycosylation  states.  With  more  glycosylation  sites,  the  EPO protein  will  be  more  stable  and  also  increase  its  half-life.  A construct  of  recombinant  human  erythropoietin  (rhEPO)  which contains 2 additional N-link for glycosylation were designed. Based on translation analysis using ORF (open reading frame)-finder and protein  alignment  analysis  using  blast-p  of  NCBI  home  page, expected  recombinant  hEPO  with  additional  6-histidin  tag  in carboxyl terminus  was expressed. HEK293T cells  were transfected with  recombinant  plasmid  containing  rhEPO  by  using  calcium phosphate method. Expression of rhEPO was detected by dot blot and  Western  blot  analysis  using  hEPO  antibody  as  the  primary antibody  and  antirabbit  antibody  with  alkaline  phospatase  linked as  the  secondary  antibody.  The  bands  were  detected  by BCIP/NBT color  development  substrate.  The  data  indicated detection of EPO in culture medium of transfected HEK293T cells.Key  words:  HEK293T  cell,    calcium    phosphate    transfection,  N-linked glycosylation, recombinant human erythropoietin